APPRAIZING THE COACHING BEHAVIORS OF COACHES IN A STATE UNIVERSITY - Tabao, Mark John (International Journal of Arts, Sciences and Education, 2022)
Abstract Previous research on coaching behavior concentrated on defining the qualities and types of coaching behaviors as well as the antecedent elements that influence coaching behaviors. Now, research is needed to explain the effects or impacts of coaching behavior. This study was descriptive-correlational. This design describes coaches’ profiles and coaching habits. The correlational design aimed to establish the relationship between two or more variables. This study shows the importance coaches have on athlete conditioning. This means training and conditioning programs are only intense during competition seasons. Athletes appreciate coaches’ technical ability. In response, coaches emphasize technical skills. It also revealed that university coaches allow athletes to help develop goals and methods. The training and instruction centered coaching approach showed moderate relation to all coaching behaviors, with goal setting highest. This means that if a coach focuses on training and instruction, they also perform other coaching behaviors. Autocratic coaching did not correlate with any coaching behavior. Autocratic coaches avoid training and conditioning, technical skills, mental preparation, and goal planning. Autocratic coaches decide without player input. The coaching behavior scale indicates decision-making practices.